Anogenital distance predicts sexual odour preference in African giant pouched rats. (February 2019) - Freeman, Angela R.; Sheehan, Michael J.; Ophir, Alexander G.
Abstract : Identifying reproductively viable partners may be the most important aspect of searching for a mate. When females vary in their reproductive receptivity, it is incumbent upon males to discriminate among females based on the likelihood of successful copulation and fertilization. We have observed that female African giant pouched rats ( Cricetomys ansorgei ) demonstrate profoundly delayed sexual development, with some adults exhibiting a highly neotenous, fully fused vagina. To say that the lack of vaginal patency presents a barrier to mating is a tremendous understatement. Based on this unique observation, we tested male preferences towards urine collected from patent and nonpatent females. We found that males with longer anogenital distances (AGD; a proximate measure of developmental masculinization) show differential interest towards patent and nonpatent females, preferring patent females. Strikingly, males with short AGDs did not show any differential interest between female odours. Correspondingly, only patent females demonstrated reduced interest in odour from short AGD males; nonpatent females did not demonstrate a preference. Our study demonstrates that pouched rats show differential interest in odours closely associated with mate quality. We are the first, to our knowledge, to show that the AGD of the evaluator enhances mate preferences and influences their interest in potential mating partners. Highlights: Male giant pouched rats determined female sexual receptivity using odour cues. Masculinized males differentially investigated receptive/unreceptive females' odours. Receptive females differentially investigated masculinized/feminized males' odours.